Antioxidant and antimicrobial profile of chicken sausages prepared after fermentation of minced chicken meat with Lactobacillus plantarum and with additional dextrose and starch. (April 2017) - Geeta,; Yadav, Ajit S.
Abstract: Lactobacillus plantarum, one of the most resourceful probiotic bacteria which has been known for its antioxidant and antimicrobial property. The aim of this study was to assess the antioxidant and antimicrobial properties of L. plantarum with the use of dextrose and starch as a substrate in chicken sausage prepared before and after fermentation of minced chicken meat with L. plantarum . Results indicated that chicken sausages prepared after fermentation of minced chicken meat (without spices) supplemented with dextrose and starch and fermented with L. plantarum showed higher antioxidant scavenging activity against hydroxyl, superoxide anion (SASA) and DPPH free radicals activity of L. plantarum both in fermented raw minced chicken meat and cooked chicken sausage as compared to those groups without addition of sugars. The minced chicken meat supplemented with dextrose and starch subjected to fermentation with L.plantarum also showed lower lipid oxidation as well better scores for sensory as well as lower microbial counts as compared to sausages prepared from fermented minced chicken meat without addition of sugars. However, combinations of sugars exerted better antioxidant and antimicrobial effect than using singly. The results indicated usefulness of sugars in enhancing the antioxidant and antimicrobial potential of L. plantarum i n minced chicken meat during fermentation. Highlights: Minced chicken meat was fermented incorporating dextrose and starch with Lactobacillus plantarum . Chicken sausages were prepared after fermentation of chicken meat. Combination of dextrose and starch exerted higher antioxidant and antimicrobial effect. Novel method exploiting higher fermentative potential was standardized.